Size and morphology of sella and volumetric evaluation of pituitary gland: a radiological survey - Goyal, Diksha M.; Nagapurkar, Abhijeet D. (International Journal of Research in Medical Sciences, 2022)
Background: Sella turcica is an important anatomical structure in the middle cranial fossa. It’s size follows the size of pituitary gland. The present study aimed to evaluate the size and morphology of sella and pituitary gland in the same patients without known hormonal or pituitary pathology. Methods: In this cross-sectional observational study three hundred patients underwent lateral x-ray of skull for sella turcica measurements and MRI brain for pituitary gland measurements. Results: We observed normal shape of sella (round or oval) in 66.7% of the study participants. Maximum mean anterior-posterior (AP) dimension was seen in the age group of 41 to 50 years (1.24±0.19 cm), while maximum length (0.87±0.12 cm), depth (0.87±0.21 cm) and volume (0.49±0.21 cu cm) was observed in the age group of 51 to 60 years. Similarly, CC dimension was observed to be maximum in the age group 41 to 50 years (5.9±0.51 mm). Study participants of age group more than 60 years had the maximum mean transverse dimension (12.73±0.29 mm) and the pituitary volume on MRI was observed to be maximum for the age group 51 to 60 years (398.45±61.24 cu mm). Conclusions: In our sample of 300 patients, sella turcica was normally shaped in 66.7%. Various dimensions of sella turcica and pituitary gland increased significantly till 50 to 60 years of of age, after which they decreased.